Simulation of Zeta Converter Based 3-level NPC Inverter with PV System - D. Selvabharathi; Palanisamy R; K. Selvakumar; V. Kalyanasundaram; D. Karthikeyan; Amal Nair; Kriti Karnavat; Annanya Sharma (Institute of Advanced Engineering and Science, 2018)
This paper proposes increasing the efficiency of the autonomous Photovoltaic (PV) system by utilizing zeta converter alongside neutral point clamped multilevel inverters (NPC-MLI) based on innovative PWM scheme. The PV system acts as an input source and the relevant control of zeta converter through maximum power point tracking (MPPT) offers the maximum available power from the PV array connected to DC-link. To obtain a high voltage gain we need to exhaust the dc-link voltage as much as possible and reduce stress on the switches. For this the NPC-MLI algorithm approaches PWM technique to perform capacitive charging in parallel and discharging in series to obtain maximum voltage gain. The proposed scheme is designed and verified via detailed simulations in the MATLAB/Simulink environment.